Task-based language learning and teaching: Theoretical, methodological, and pedagogical perspectives - Bell, Philippa (Canadian journal of applied linguistics, 2009)
The book is divided into three sections based on the area of research interest: classroom-based research, language and cognition, and task-based assessment. Krüger used the think-alouds to further understand the cognitive processes that learners use when solving problems, but from the think-aloud data, she also suggested that our socio-cultural contexts affect how we learn a language. Heine's research does not focus on foreign language learning processes, but the relationship between general and linguistic problem-solving during the processing of subject-specific tasks.